High‐normal unconjugated bilirubin is associated with decreased risk of chronic kidney disease in type 2 diabetes: A real‐world study - Xu, Man‐Rong; Jin, Chun‐Hua; Lu, Jun‐Xi; Li, Mei‐Fang; Li, Lian‐Xi (Diabetes/metabolism research and reviews, 2023)
Objective To investigate the association between serum unconjugated bilirubin (UCB) within normal limits and chronic kidney disease (CKD) in T2DM patients. Method This cross‐sectional, real‐world study was performed in 8661 hospitalised T2DM patients. The subjects were stratified into quintiles based on serum UCB levels. The clinical characteristics and CKD prevalence were compared among the UCB quantile groups. The associations of serum UCB levels and quintiles with CKD were also analysed by binary logistic regression. Results After controlling for age, sex, and diabetes duration (DD), the CKD prevalence (20.4%, 12.2%, 10.6%, 8.3%, and 6.4% for the first, second, third, fourth, and fifth quintiles, respectively, p < 0.001 for trend) was significantly decreased across the serum UCB quintiles. The fully adjusted regression model showed negative associations of serum UCB levels (OR: 0.660, 95% CI: 0.585–0.744; p < 0.001 for trend) and quintiles (p < 0.001) with the presence of CKD. Compared with the subjects in the lowest UCB quintile, the risk of CKD decreased by 36.2%, 54.3%, 53.8%, and 62.1%, respectively, in those from the second to the highest UCB quintile. Additionally, C‐reactive protein (CRP) levels were significantly higher in the subjects with CKD than in those without CKD (p < 0.001), and significantly decreased across the UCB quintiles (p < 0.001 for trend). Conclusions Serum UCB levels within the normal range were significantly and negatively linked to CKD in T2DM patients. High‐normal UCB may be an independent protective factor for CKD by its antioxidant and the following anti‐inflammatory activities through its signalling activity, which was indicated by clearly decreased CRP levels across the UCB quintiles.